Th17 Cells in Immunity and Autoimmunity - Simone Kennedy Bedoya; Brandon Lam; Kenneth Lau; Joseph Larkin (Clinical and Developmental Immunology)
Th17 and IL-17 play important roles in the clearance of extracellular bacterial and fungal infections. However, strong evidence also implicates the Th17 lineage in several autoimmune disorders including multiple sclerosis, psoriasis, rheumatoid arthritis, inflammatory bowel disease, systemic lupus erythematosus, and asthma. The Th17 subset has also been connected with type I diabetes, although whether it plays a role in the pathogenicity of or protection from the disease remains a controversial issue. In this review we have provided a comprehensive overview of Th17 pathogenicity and function, including novel evidence for a protective role of Th17 cells in conjunction with the microbiota gut flora in T1D onset and progression.